Development of Interactive Multimedia on Chemical Bonding Material - Iwan; Enawaty, Eny; Masriani (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The limited availability of learning media capable of facilitating students’ understanding of abstract concepts in chemical bonding prompted this research. This study aims to determine the validity level of the developed interactive multimedia and to assess teachers’ and students’ responses toward its use. The research employed a Research and Development (R&D) method using a modified ADDIE model, limited to the development stage. The trial subjects consisted of two chemistry teachers and 9 students for the small-scale test, as well as 30 students from grade XI at SMAN 2 Sekadau for the large-scale test.The validation results from experts indicated that the interactive multimedia was highly valid with an average percentage of 94.17%, consisting of 88.33% for the media aspect, 96.25% for the material and language aspects, and 97.92% for the assessment aspect. Student responses reached an average of 90.69% in the small-scale test and 94.53% in the large-scale test, while teacher responses reached 83.07%.The novelty of this research lies in the use of interactive multimedia equipped with a variety of engaging features, such as ice-breaking activities and educational games, which are rarely implemented in chemical bonding learning at the senior high school level. Therefore, the developed interactive multimedia can be used as a learning medium and further tested for its effectiveness.